(untitled) (Academicia Globe: Inderscience Research, 2023)
A joint with a key is said to be connected with a shaft and a hole installed on it using a key, i.e. prismatic, wedge-shaped or segmental cross-shaped details. A key joint can be a stressed or unstressed joint. A joint with a tension key develops compressive stress until the load is applied.